Digestibility of nutrients, balance of nitrogen and growth performance in dairy heifers fed mixed forage diets - RADOTRA, SUDESH; KATOCH, B S; SHARMA, V K (The Indian Journal of Animal Sciences, 2014)
Guinea grass (panicum maximum Jacq. PGG 9) and green panic grass (Panicum maximum Trichoglume HGP 2) were intercropped with ,oybcan with 3 replications and distributed in to 2 tn:atments, viz. T1-guinea grass -T2- soybean, and T2 green panic grass 1- soybean in completely randomized block design. Growing crossbred heifers (10; Jersey x Red Sindhi) of age 7-10 months with average body weight of 58-65 kg were divided on the basis of weight in above 2 treatment groups. The grasses along with soybean fodder were harvested fresh and evaluated ior green lind dry biomass production. The green and dry matter productions were 35.17±0.82 and 7.47±0.16 t/ha in guinea grass + soybean and 29.87±0.78 and 5.94±0.14 tiha in green panic grass + soybean respectively. The herbage mixtures were chaffed, mixed and fed to the animals. Chemical composition of the herbage mixtures, dry-matter intake, nutrients digestibility and growth performance in animals Were estimated. Guinea gross + soybean produced significantly (P<0.05) higher green and dry biomass. The crude protein content in both the herbage mixtures was ranging 10.78 to 11.43%. Green panic grass+ soybean mixture had higher ether extract content and gross energy than other herbage mixture. The herbage mixtures had higher total ash content reflecting the higher mineral status. Green panic grass + soybean contained lower eontcnts of ADF, cellulose, lignin and silica and higher contenl of calcium as compared to guinea grass + soybean. The dry-matter intake (DMI) kg/ 100 kg body weight was significantly higher in group T2 (3 .176±0.11) than group T1 (2.882±0.05) herbage mixture. The digestibility coefficients of CP, CF, ADF, hcmicellulose and cellulose in group T 2 were significantly (P<0.05) higher than group T1. The DCP and TDN in groups TI and T, were 6.74±0.16 and 52.81±0.76 and 7.66±0.11 and 54.04±0.85%, respectively. Positive nitrogen balance in both the groups indicated that both the herbage mixtures were able to support maintenance and modest growth requirements in the experirnental heifers. There was no significant difference in growth rate (368.06±49.45 and 398.66±38.11 g/ head/day) of animals between the treatments. Green panic grass + soybean herbage mixture was more nutritious than the guinea grass + soybean herbage mixture for animals, however, the green and dry biomass production was significantly (P<0.05) higher in guinea grass + soybean. Therefore, it can be inferred from the experiment that perennial grasses can be transplanted and intercropped with legume fodders in wastelands for higher biomass yield and quality fodders for the animals.